Accuracy and prognostic impact of FDG PET/CT and biopsy in bone marrow assessment of follicular lymphoma at diagnosis: A Nation‐Wide cohort study. (13th November 2022) - Ródenas‐Quiñonero, Isabel; Chen‐Liang, Tzu; Martín‐Santos, Taida; Salar, Antonio; Fernández‐González, Marta; Celades, Carolina; Navarro, José‐Tomás; Martínez‐Garcia, Ana Belén; Andreu, Rafael; Balaguer, Aitana; Martin García‐Sancho, Alejandro; Baile, Mónica; et al.
Abstract: Backgound: In the workup of follicular lymphoma (FL), bone marrow biopsy (BMB) assessment is a key component of FLIPI and FLIPI2, the most widely used outcome scores. During the previous decade, several studies explored the role of FDG‐PET/CT for detecting nodal and extranodal disease, with only one large study comparing both techniques. Methods: The aim of our study was to evaluate the diagnostic accuracy and the prognostic impact of both procedures in a retrospective cohort of 299 FL patients with both tests performed at diagnosis. In order to avoid a collinearity bias, FLIPI2 was deconstructed in its founding parameters, and the bone marrow involvement (BMI) parameter separately included as: a positive BMB, a positive PET/CT, the combined "PET/CT and BMB positive" or "PET/CT or BMB positive". These variables were also confronted independently with the POD24 in 233 patients treated with intensive regimens. Results: In the total cohort, bone marrow was involved in 124 and 60 patients by BMB and PET/CT, respectively. In terms of overall survival, age > 60 y.o. and the combined "PET/CT or BMB positive" achieved statistical independence as a prognostic factor. In patients treated with an intensive regimen, only the combined "PET/CT or BMB positive" added prognostic value for a shorter overall survival, when confronted with the POD24. Conclusion: Our results show that in FL both BMB and PET/CT should be considered at diagnosis, as their combined assessment provides independent prognostic value in the context of the most widely use clinical scores.